(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
The primary motivation for initiating this study is the recognition that there is a lack of geographically disaggregated information regarding the socio-economic effects of COVID-19 and thus resulted in failing to cultivate context-based prevention response and the prevailing prevention needs. Unless the key socio-economic effects of COVID 19 are known, and if there is no alignment with the spatial variation, it is impossible to plan, target, and deliver sound interventions. This study covers North Shewa Zone of Oromia region, Ethiopian. Mixed research approach with descriptive survey design has been used and systematic sampling technique was employed to select respondents proportionally from each stratum by the population size determination formal of Yemane (1967) the sample unites were 374 respondents. The study revealed that Covid -19 has significant effect of the social networking specifically; on social assets, social gathering.